Pengembangan Industri Baru Terhadap Perekonomian Masyarakat - Dwi Ariska (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Industrial development in Indonesia is currently taking place very rapidly in line with the advancement of the technological era with the establishment of large companies with very sophisticated equipment and the continuous improvement of several sectors, such as agriculture, education, property, handicrafts and weaving. Industry can be defined as an economic activity that processes raw materials or semi-finished goods into goods of higher value. Development is a process of change that is planned as one of human efforts to improve the quality of life. Likewise, national development is closely related to the country's ability to utilize its resources, either with the help of technology or without the help of technology. National development is essentially multidimensional, involving various sectors such as education, agriculture, health, industry and so on. The Industrialization process is a process of socio-economic change that changes the livelihood system of an agrarian society into an industrial society. Industrialization can also be interpreted as a situation where society focuses on the economy which includes increasingly diverse jobs (specialization), higher salaries and income. Industrialization is part of the modernization process where social change and economic development are closely related to technological innovation